2021
DOI: 10.1002/aoc.6288
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted fabrication of a mixed‐ligand [Cu43‐OH)2]‐cluster‐based metal–organic framework with coordinatively unsaturated metal sites for carboxylation of terminal alkynes with carbon dioxide

Abstract: The development of efficient and stable metal–organic framework (MOF) catalysts with coordinatively unsaturated metal sites for modern organic synthesis is greatly important. Herein, a robust [Cu4(μ3‐OH)2]‐cluster‐based MOF (Cu‐MOF) with a mixed‐ligand system was successfully fabricated by a microwave‐assisted method under mild conditions. The as‐prepared Cu‐MOF catalyst possessing unsaturated Cu (II) sites exhibited excellent catalytic activity toward the direct carboxylation of 1‐ethynylbenzene with CO2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The microwave synthesis process is user-friendly, the reaction time is short (hours or minutes), the energy distribution is uniform, and the crystal size and morphology are easy to control. 98 Compared with other synthesis methods, this method adds precision instruments to control the microwave energy, but it is more environment-friendly and energy-saving while producing high yield and performance products. 99,100…”
Section: Mofs and Mofs-based Catalystsmentioning
confidence: 99%
“…The microwave synthesis process is user-friendly, the reaction time is short (hours or minutes), the energy distribution is uniform, and the crystal size and morphology are easy to control. 98 Compared with other synthesis methods, this method adds precision instruments to control the microwave energy, but it is more environment-friendly and energy-saving while producing high yield and performance products. 99,100…”
Section: Mofs and Mofs-based Catalystsmentioning
confidence: 99%
“…Suction is then used to filter and dry precipitates. Some MOFs that were synthesized by using the microwave method are Fe-MIL-53, ZIF-8, Fe-MIL-101-NH2, MIL-100 and UiO-66 [83][84][85] .…”
Section: Microwave Synthesismentioning
confidence: 99%
“…They controlled the reaction time to probe the crystal formation process and applied them for the immobilization of atmospheric CO 2 due to their unique physical and structural properties. Chen et al synthesized MOF-74 (Ni) using MW-assisted, hydrothermal and condensation reflux methods, respectively [257] . By comparison, it was found that MW could shorten the synthesis time from 32 h and 24 h to 1 h, which greatly improved the reaction efficiency.…”
Section: Microwave-assistedmentioning
confidence: 99%